PENGARUH PENGENDALIAN INTERNAL, PEMANFAATAN TEKNOLOGI INFORMASI, DAN AKUNTABILITAS TERHADAP TRANSPARANSI PENGELOLAAN DANA DESA - Ramdhana, Dara; Asmara, Jhon Andra (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
This study aims to analyze simultaneously and partially the variables of Internal Control, Utilization of Information Technology, and Accountability to the Transparency of Village Fund Management during the Pandemic Period (Study on Villages in Bireuen Regency). This type of research is a quantitative study with a sample of 172 respondents consisting of the village head/village secretary and the head of financial affairs (treasury). The research data were collected through questionnaires, processed and analyzed using multiple linear regression analysis using SPSS version 25 program. The sampling technique used was simple random sampling. The results of this study indicate that Internal Control partially has a positive effect on the Transparency of Village Fund Management. The partial use of Information Technology has a positive effect on the Transparency of Village Fund Management. Accountability partially affects the Transparency of Village Fund Management. Internal Control, Utilization of Information Technology, and Accountability simultaneously affect the Transparency of Village Fund Management.